STRATEGI PENGELOLAAN LINGKUNGAN SEKOLAH YANG SEHAT DI WILAYAH PESISIR: STUDI KASUS DI SDN 107427 PEMATANG GUNUNG - Jihan Fadhilah Harahap; Nur Hafizah Azzahro; Rapotan Hasibuan; Indah Nurhaliza; Mafaza Auliya Lubis; Aura Deby Sang Ilahi (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
School environmental hygiene is an important indicator in supporting a healthy and comfortable learning process. A dirty environment can be a source of disease and create an atmosphere that is not conducive to students. This outreach program was implemented in response to various environmental health issues found at SDN 107427 Pematang Gunung. Based on initial surveys and situation analysis, the main issue faced was the habit of littering, which impacts the comfort and health of the learning environment. The public health student group conducted this activity in an educational and participatory manner. The activities included providing materials using visual media, interactive quizzes, waste sorting, ice-breaking activities, and providing creatively designed segregated waste bins. Students were given pre- and post-campaign tests to measure changes in knowledge and behavior. Evaluation results showed that students became more aware of school environmental cleanliness. One example was an increase in the number of students aware of scattered trash (from 63% to 84%) and an increase in behavior reminding peers (from 83% to 93%). Additionally, negative behaviors such as writing on walls and desks decreased. This activity demonstrates that clean and healthy habits in schools can be fostered in an enjoyable and student-centered manner. It is hoped that such activities will be repeated to strengthen a clean culture within the educational environment.